Adsorption of phenol from aqueous solutions on original and oxidized multiwalled carbon nanotubes - Przemysław Podkościelny; Andrzej Dąbrowski (Adsorption Science & Technology)
The surface heterogeneity of the multiwalled carbon nanotubes is investigated on the basis of adsorption isotherms from dilute aqueous phenol solutions at various temperatures. The Dubinin–Astakhov isotherm connected with the non-symmetrical distribution function of adsorption energies has been applied to describe adsorption equilibrium. Theoretical isosteric heats of adsorption connected with the Dubinin–Astakhov isotherm have been estimated as well. It is known that the decrease of the isosteric heat of adsorption with adsorbate loading is characteristic for the energetically heterogeneous surfaces. Theoretical description of kinetics is based on the Statistical Rate Theory of Interfacial Transport. The Statistical Rate Theory approach links the rate of transport between two phases with the difference in the chemical potentials of the molecules in these phases. Theoretical studies were verified successfully using the literature experimental adsorption data.